2019
DOI: 10.1136/jnnp-2019-320846
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic hypotension and REM sleep behaviour disorder: impact on clinical outcomes in α-synucleinopathies

Abstract: ObjectiveReview the effect of orthostatic hypotension (OH) and rapid-eye-movement sleep behavioural disorder (RBD) on survival, cognitive impairment and postural stability, and discuss pathogenic mechanisms involved in the association of these two common non-motor features with relevant clinical outcomes in α-synucleinopathies.MethodsWe searched PubMed (January 2007–February 2019) for human studies of OH and RBD evaluating cognitive impairment, postural instability, and survival in Parkinson’s disease (PD), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 53 publications
2
60
0
Order By: Relevance
“…19 This analysis, however, suggests that the different magnitude of benefit to rivastigmine in these populations may be at least in part accounted for by the relative differences in OH prevalence: higher in PDD compared to AD. 20 Furthermore, the presence of OH as a prominent marker of a "malignant" disease phenotype 20 may also explain prior analyses demonstrating a significantly greater response to rivastigmine among patients with more rapid disease progression. 21 An intriguing finding was the significantly larger cognitive benefit in patients with OH+ versus OHpatients for the capsule compared to the patch formulation at 76 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…19 This analysis, however, suggests that the different magnitude of benefit to rivastigmine in these populations may be at least in part accounted for by the relative differences in OH prevalence: higher in PDD compared to AD. 20 Furthermore, the presence of OH as a prominent marker of a "malignant" disease phenotype 20 may also explain prior analyses demonstrating a significantly greater response to rivastigmine among patients with more rapid disease progression. 21 An intriguing finding was the significantly larger cognitive benefit in patients with OH+ versus OHpatients for the capsule compared to the patch formulation at 76 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…This is of interest as RBD is specifically associated with alpha‐synucleinopathies and the GBA1 mutation carriers of the RBD cohort had a 3.2‐fold higher phenoconversion rate from RBD to parkinsonism and/or dementia than non‐ GBA1 carriers . Moreover, a recent review reported RBD to be positively associated with a more severe “malignant” phenotype, including cognitive impairment in PD and DLB . With more evidence arising, PD GBA seem to be a model for a malignant phenotype in PD.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, a recent review reported RBD to be positively associated with a more severe "malignant" phenotype, including cognitive impairment in PD and DLB. 13 With more evidence arising, PD GBA seem to be a model for a malignant phenotype in PD.…”
Section: Discussionmentioning
confidence: 99%
“…RBD in PD patients and the akinetic PD subtype were found to be associated with impaired cognitive function in many studies ( Svenningsson et al, 2012 ; Jozwiak et al, 2017 ; Pilotto et al, 2019 ). Accordingly, overall cognitive performance particularly affecting visuospatial function, executive function, attention, and memory in PD patients with RBD compared to those without was demonstrated ( Huang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%